-2-13=3

Simple and best practice solution for -2-13=3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2-13=3 equation:


Simplifying
-2 + -13 = 3

Combine like terms: -2 + -13 = -15
-15 = 3

Solving
-15 = 3

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 2t-9=-2+3t-1 | | 70/20=50/x | | -17/23=n/23 | | 19-19a= | | 14x-2(2x-2)=14 | | 8g+7=-9+10g | | 12x+6=13x+4 | | x-39=3x/4 | | -16t^2-2t+409=370 | | 6x^2-12=6x | | 8+6m=7m | | 4(x^2-1)+2=38 | | -2r+10=-6r-10 | | 14-6x=2-x | | k^2-4k-59=-10 | | 3c+9+5c=22 | | F(x)=3+2x-5x^2 | | 2.75m-1.75m-75=140 | | 8d=7d-5 | | x*-4x-45=0 | | -22+4x=x-2(x-4) | | 9w=8+10w | | C(8)=250+1500(8)-0.002x^2 | | 5d+2.5=65 | | 7z-4z=12+3z | | 9c-4=10c | | 4k^2=48k-128 | | -8b=-4-7b | | ln(((3x^2)-4)/x) | | 11(2-x)=33 | | 4y^2+32y+48=0 | | 4a-64=44 |

Equations solver categories